Crisis of Capital, Austerity and Education in Brazil (Research, Society and Development, 2021)
The aim of this article is to analyze how the austerity policies were taken, in Brazil and in others countries, as the main strategy of overcome of effects unleashed for the global crisis of capital occurred in 2008, and how the adoption of these measures impacted at many social sections, in the spotlight the Education. Statistical datas were used for this task from Central Bank and also Transparency Portal, besides the bibliographic review that listed authors as Antunes (2015); Blyth (2017); Carcanholo (2010) and Rossi et al. (2019). The performed study indicated that the austerity process in Brazil reached particular outlines in relation to others countries and that process failed to get the promised economic development. Also it was verified that the austerity surpasses ephemeral policies of fiscal retraction, featuring as a pillar of neoliberalism at its current stage of development. In Education, the fiscal retraction represents a obstacle to the overcome of historical inequalities and puts in check structuring state policies of the section.